2021
DOI: 10.1091/mbc.e20-10-0635
|View full text |Cite
|
Sign up to set email alerts
|

Roles for ELMOD2 and Rootletin in ciliogenesis

Abstract: ELMOD2 is a GTPase activating protein (GAP) with uniquely broad specificity for ARF family GTPases. We previously showed that it acts with ARL2 in mitochondrial fusion and microtubule stability and with ARF6 during cytokinesis. Mouse embryonic fibroblasts deleted for ELMOD2 also displayed changes in cilia related processes including increased ciliation, multiciliation, ciliary morphology, ciliary signaling, centrin accumulation inside cilia, and loss of rootlets at centrosomes with loss of centrosome cohesion.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(60 citation statements)
references
References 138 publications
8
50
2
Order By: Relevance
“…ELMOD2 localizes to the basal body, and our study showed ELMOD3 localizes to cilium (Turn et al, 2021). Taking into account the fact that RPI-2 and ELMD-1 are GAPs, and loss of these two GAP proteins likely result in the overactivation of their target G proteins, how does WDR-31 function with these GAP proteins?…”
Section: Functional Redundancy Between Wdr-31 Elmd-1 and Rpi-2mentioning
confidence: 81%
“…ELMOD2 localizes to the basal body, and our study showed ELMOD3 localizes to cilium (Turn et al, 2021). Taking into account the fact that RPI-2 and ELMD-1 are GAPs, and loss of these two GAP proteins likely result in the overactivation of their target G proteins, how does WDR-31 function with these GAP proteins?…”
Section: Functional Redundancy Between Wdr-31 Elmd-1 and Rpi-2mentioning
confidence: 81%
“…The copyright holder for this preprint this version posted June 11, 2021. ; https://doi.org/10.1101/2021.06.10.445528 doi: bioRxiv preprint Furthermore, the ciliary roles of these two GAP proteins might be independent of their GAP activities, and consistent with this idea, the recent study showed the ciliary roles of ELMOD2 are partially independent of its GAP activity (Turn et al, 2021). However, a variety of evidence suggests that WDR31 and ELMOD3 do not form a complex.…”
Section: Functional Redundancy Between Wdr-31 Elmd-1 and Rpi-2mentioning
confidence: 88%
“…One is to interact with the centrosome and function in the control of ciliogenesis and control of the number and timing of cilia [113]. Another is the maintenance of retinal receptor cell.…”
Section: Rootlets-roles In Basal Body Positioningmentioning
confidence: 99%